Distribusi Tenaga Kerja Sektor Pertanian pada Basis Agroekosistem Lahan Kering - Sugiarto, Sugiarto (Jurnal Penelitian Pertanian Terapan, 2011)
The research of labor forces in village has never been released to national development strategic. So that, the amount of labor forces absurption must be solved wiht oppening job opportunity outside agriculture sector. This reseach gave information of labor force in agriculture sector and village on dry land basis. This research showed that job participation an unemployment level, nationally. Didn?t change.In horticulture dry land basis, the role of agriculture sectors were still dominated job opportunity than outside agriculture. Nevertheles, hosehold job opportunity in the village has a lot of variety and replaced the the role of job opportunity in agruculture sectors. In the other hand, work group of in agriculture sector was more dominated with lower education from down elememtary school and it could not complete in labor force market outside agriculture sector. So, that, the role of agriculture sectors was still improtant to solve labor force problem in villages and still become a burden if it?s not balanced with labor absorption in outside agriculture sector. Keywords : Labor force, agriculture, dry land agroecosystem